A Model of Johannine Ethics - Bennema, Cornelis (Studies in Christian ethics, 2022)
Johannine ethics was a problematic topic for a long time and has only been an acceptable and fruitful area of research since 2012. To stimulate and guide future research, this article proposes a model of Johannine ethics that consists of five aspects: (1) Graeco-Roman virtue ethics is the broad ethical context for Johannine ethics; (2) family is the theological context for Johannine ethics; (3) mimesis is central to Johannine ethics; (4) moral reasoning is the cognitive route to ethics; (5) Spirit and community empower ethical living. The argument is that the Johannine writings present ethics as divine family education that has mimesis at its centre and is facilitated by moral reasoning and the Spirit as the moral force. An Appendix contains a list of publications on Johannine ethics between 2012 and 2022.